Observation Of Regional Language Use Patterns In Daily Interactions In Padang Traditional Markets - Saputra, Miskal Ade; Ilahi, Rahmat; Tuljnnah, Zahra (Universitas PGRI Sumatera Barat, 2025)
Regional languages are an important element in the formation of the social and cultural identity of local communities. In the midst of modernization, urbanization, and the dominance of Indonesian as the national language, the use of regional languages is experiencing interesting dynamics to be studied. Informal public spaces such as traditional markets are strategic places to observe people's natural language practices. This study aims to describe and analyze the pattern of use of regional languages, especially Minangkabau languages, in daily interactions between sellers and buyers in traditional markets in Padang City. This study uses a qualitative approach with participatory observation methods and speech recording. Data were collected through direct observation of verbal interactions, dialogue recording, and audio documentation with the informant's permission. Data analysis was carried out using a sociolinguistic approach with a focus on language selection, code switching, and code mixing. The results show that the Minangkabau language still dominates verbal interaction in traditional markets, especially in informal situations and between local speakers who share the same cultural background. Bahasa Indonesia is used selectively and strategically, especially when interacting with immigrant buyers, non-Minangkabau speakers, or in situations that demand clarity of meaning and more formal politeness. The phenomenon of code switching and code mixing is found quite frequently and reflects the speaker's linguistic flexibility in adapting the language to the social context, communication goals, and characteristics of the opponent. These findings show that traditional markets not only function as a center of economic activity, but also as a social and cultural space that plays an important role in maintaining the sustainability and vitality of regional languages in the midst of social changes in urban society.